Efficient Isolation of Dihydropyranocoumarins and Simple Coumarins from Mutellina purpurea Fruits - Skalicka-Woźniak, Krystyna; Mroczek, Tomasz; Walasek, Magdalena; Głowniak, Kazimierz (Planta Medica, 2016)
For the first time, the separation of coumarin derivatives from the petroleum ether extract of the fruits of Mutellina purpurea through high-performance countercurrent chromatography (HPCCC) is described. Four compounds, pteryxin (1; 2.72 mg), hyuganin C (2; 7.94 mg), osthol (3; 4.30 mg), and hyuganin A (4; 3.09 mg), were obtained in a single run following the injection of crude extract (300 mg). Additionally, auraptenol (5) and hyuganin D (6) were identified using LC-ESI-(Q)TOF-MS. The structures of the isolated compounds were elucidated through spectroscopic (NMR and MS) methods. This is apparently the first report of the identification of dihydropyranocoumarins in this plant, and the first time that HPCCC was used to separate them.
Keywords: Mutellina purpurea; Apiaceae; high-performance countercurrent chromatography; dihydropyranocoumarins; coumarins; spectroscopic analysis